Reconsidering Urban Densification for Microclimatic Improvement: Planning and Design Strategies for Istanbul - Okumus, Deniz Erdem; Terzi, Fatih (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2022)
One of the key issues of the urban planning agenda is how urban density be decided in the spatial configurations of future neighbourhoods to overcome complex challenges such as urban warming. This paper aims to reconsider urban density as a spatial planning instrument to develop effective densification policies, planning and design strategies in terms of surface urban heat island (SUHI) mitigation in Istanbul. The quantitative research embraced a four-stage methodology including grid-based sampling design, decoding the taxonomy of urban density-matrix (UDM), land surface temperature mapping, and ANOVA tests. Tests were conducted on the UDM consisting of nine building typologies representing the horizontal and vertical urban density. The research indicated that the impact of urbanisation on SUHI can be mitigated by controlling densities and urban forms based on quantitative findings. The highest temperatures were recorded in areas with high-coverage-mid-rise and mid-coverage-mid-rise development. The different levels of SUHI in different building typologies having the same density indicated the mitigation potentials of the built-form in Istanbul's local urban warming. Low coverage and high-rise building forms were an optimal solution for mitigating SUHI in densely populated urban areas. The research gives insight into an ongoing debate among urban professionals in Istanbul concerning the impacts of density and the urban form for climate adaptation. It enables professionals to understand the impact of urban planning decisions on microclimate and integrate them into the operational processes. Considering quantitative research findings as a strong foundation for developing policy recommendations and using them as a guideline may create new opportunities for researchers, practitioners, and policymakers. The study has an original value for exploring design strategies to improve microclimate and promoting sustainable urban development.
Keywords: Istanbul; spatial planning; urban density; urban design; urban heat island; LAND-SURFACE TEMPERATURE; HEAT-ISLAND; CLIMATE-CHANGE; BUILDING HEIGHT; CANYON GEOMETRY; COVER PATTERN; DENSITY; IMPACT; CITY; ENERGY; Architecture